Child and Adolescent Online Mental Health Information: Parent and Adolescent Perspectives to Inform Development of Canadian Mental Health E-Resources for Paediatrics. (1st June 2016) - Jovanovic, M; Monga, S; Korczak, D; Grewal, S
Abstract: BACKGROUND: Parents and adolescents are searching online for information about mental health. Google searches are frequently used, but do not always yield accurate and reliable information that is presented in a user-friendly manner. The first step toward the development of a useful online child mental health resource is to examine existing web content and understand parent and adolescent needs from online mental health material. OBJECTIVES: The objectives of this study are two-fold (i) To conduct an environmental scan of existing online repositories of child and adolescent mental health information with respect to both parent and adolescent friendly content on three identified topic areas for the initial phase of the project (Anxiety, Eating Disorders, Suicide Prevention) (ii) To determine parent and adolescent needs from, and perspectives about, current web-based information with respect to site design, content and limitations to inform the creation of a pediatric hospital based web site with a broad range of information pertaining to child and adolescent mental health. DESIGN/METHODS: An environmental scan was conducted to assess available online information about three identified topic areas as described above. As the project continues, the scan will be expanded to include other topic areas in child and adolescent mental health. Parallel parent needs assessment surveys were conducted. As our adolescent section was being developed, adolescents were surveyed for their feedback regarding illustrations and presentation of current content. RESULTS: The environmental scan identified 17 hospital websites for in-depth review. Although some websites had information on diverse mental health topics, few contained comprehensive information on a broad range of topics. For example, only 9 had information about anxiety disorders. Additionally, an overall lack of adolescent specific content was noted. Parent surveys revealed significant interest in a strong stand-alone site where they could access mental health information. Parents also indicated that they would prefer separate parent and teen content areas. CONCLUSION: Current websites providing information regarding child and adolescent mental health, while plentiful, lack sufficient scope, adolescent-friendly content, and interactivity that limit their utility for parents and families. Development of a high-quality and accessible child and adolescent mental health website requires an interdisciplinary collaboration of experts in mental health, website design, and knowledge dissemination. This study has informed the development of a new online resource, interactive elements of which will be shared as part of the oral presentation.